Artificial Intelligence and Data Ethics in Turkıye’s Financial Sector - Topuzoğlu, Tansu; Tekin, İlknur Çevik (Fırat University, 2024)
The digital transformation of the 21st century has had a profound impact on the financial sector with the innovations it has brought. The digitalisation process, accelerated by the COVID-19 pandemic, has led to radical changes in the financial sector and accelerated the integration of advanced technologies such as artificial intelligence and data analytics. Artificial intelligence applications have been used in many areas such as customer analytics and marketing, credit scoring and risk management, fraud detection, wealth management with robo-advisory, regtech, and this technological evolution has reshaped the customer experience while increasing the efficiency of financial services. However, the use of these technologies has also raised ethical issues. The fact that AI technologies are black boxes of complex algorithms raises the question of 'AI ethics' and 'data ethics' for users and data subjects. In this situation, there is no international 'ethical standard' for artificial intelligence technologies. The fact that countries have different ethical-moral understandings prevents the formation of an international ethical standard. However, some international and national organisations publish ethical guidelines as recommendations. On the other hand, financial institutions and regulators are developing various policies and regulations to ensure that artificial intelligence and data analytics applications comply with ethical understanding. This study discusses the use of artificial intelligence technologies in the financial sector, the application areas of artificial intelligence in the Turkish financial sector, the principles and problems of artificial intelligence and data ethics. In the relationship between artificial intelligence and ethics, privacy and security, transparency and accountability, fairness and bias, and community impact are examined. In data ethics, data collection and consent, data processing and anonymity, data quality and fairness, data sharing and security are examined. In relation to data ethics, data collection and consent, data processing and anonymity, data quality and fairness, data sharing and security are analysed. In addition, international ethical guidelines, laws and regulations in the Turkish financial sector are analysed. Although there is no specific directive on artificial intelligence and data ethics in the Turkish financial sector, the Personal Data Protection Law provides the general framework for data ethics. The Banking Law and the Consumer Protection Law aim to protect consumers in financial transactions. The systems established by the Law on Payment and Securities Settlement Systems, Payment Services and Electronic Money Institutions, the Capital Market Law and the regulations of the Competition Board enable the supervision of financial transactions related to artificial intelligence. The volume and diversity of transactions in the financial sector and their impact on the economy and other sectors cannot be ignored. Given the rapid progress and changes in artificial intelligence technologies, the existing legislation will eventually become inadequate. The establishment of artificial intelligence and data ethics standards will be effective in preventing the negative effects that may occur in practice.

21. yüzyılın dijital dönüşümü, sunduğu yeniliklerle finans sektörünü de derinden etkilemiştir. COVID-19 pandemisinin hızlandırdığı dijitalleşme süreci, finans sektöründe köklü değişimlere yol açmış ve yapay zekâ ile veri analitiği gibi ileri teknolojilerin entegrasyonunu hızlandırmıştır. Finans sektöründe müşteri analitiği ve pazarlama, kredi skorlama ve risk yönetimi, sahtecilik tespiti, robo-danışmanlık ile varlık yönetimi, regtech gibi birçok alanda yapay zekâ uygulamaları kullanıma girmiş ve bu teknolojik evrim, finansal hizmetlerin etkinliğini artırırken müşteri deneyimini de yeniden şekillendirmiştir. Ancak, bu teknolojilerin kullanımı etik soruları da beraberinde getirmiştir. Yapay zekâ teknolojilerinin karmaşık algoritmalardan oluşan birer kara kutu olmaları, kullanıcılar ve etkilenenler tarafından ‘yapay zekâ etiği’ ve ‘veri etiği’ konusunu gündeme getirmektedir. Bu durumla birlikte, yapay zekâ teknolojileri için uluslararası bir ‘etik standardı’ bulunmamaktadır. Ülkelerin farklı etik-ahlak anlayışının bulunması, uluslararası bir etik standardının oluşmasına engel olmaktadır. Fakat bazı uluslararası ve ulusal kuruluşlar öneri olarak etik kılavuzları yayınlamaktadır. Finansal kurumlar ve düzenleyici otoriteler ise yapay zekâ ve veri analitiği uygulamalarının etik anlayışına uygun olmasını sağlamak için çeşitli politikalar ve düzenlemeler geliştirmektedir. Bu çalışmada, yapay zekâ teknolojilerinin finans sektöründeki kullanımı, Türkiye finans sektöründe kullanılan yapay zekâ uygulama alanları, yapay zekâ ve veri etiği hususundaki ilkeler ve sorunlar ele alınmaktadır. Yapay zekâ etik ilişkisinde; veri gizliliği ve güvenliği, şeffaflık ve hesap verebilirlik, adalet ve önyargı, toplum etkileri incelenmektedir. Veri etik ilişkisinde ise, veri toplama ve rıza, veri işleme ve anonimlik, veri kalitesi ve adalet, veri paylaşımı ve güvenlik hususları incelenmektedir. Ayrıca, uluslararası ‘etik ilkeler’ kılavuzları, Türkiye finans sektöründeki mevzuat ve düzenlemeler incelenmektedir. Türkiye finans sektöründe yapay zekâ ve veri etiğine yönelik özel bir klavuz bulunmamakla birlikte Kişisel Verilerin Korunması Kanunu veri etiği hususundaki genel çerçeveyi oluşturmaktadır. Bankacılık Kanunu ve Tüketici Koruma Kanunu ile finansal işlemlerde tüketicinin korunması amaçlanmaktadır. Ödeme ve Menkul Kıymet Mutabakat Sistemleri, Ödeme Hizmetleri ve Elektronik Para Kuruluşları Hakkında Kanun ile kurulan sistemler, Sermaye Piyasalar Kanunu, Rekabet Kurulu düzenlemeleri ise yapay zekâ ile ilişkili yapılan finansal işlemlerin denetimine imkân sağlamaktadır. Finans sektöründe gerçekleşen işlemlerin hacmi, çeşitliliği ile ekonomiye ve diğer sektörlere olan etkisi göz ardı edilemeyecek düzeydedir. Yapay zekâ teknolojilerinde ki hızlı ilerleme ve değişim düşünüldüğünde, mevcut mevzuatın bir süre sonra yetersiz kalmasına neden olacaktır. Yapay zekâ ve veri etiği standartlarının oluşturulması, uygulamada karşılaşılabilecek olumsuzlukların önüne geçmekte etkili olacaktır.
Türkiye Finans Sektöründe Yapay Zekâ Etiği ve Veri Etiği
Keywords: Finance; Finans